The Educational and Humanitarian Dimensions of the Al-Taf Incident from the Point of view of Sociology, Psychology, And Historical Structure (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The research aims to identify the educational, humanitarian and social dimensions of the Al-Taf incident from the point of view of sociology, psychology and the historical structure, which were among the objectives of the Al-Taf incident. We used the descriptive and analytical methods in the research as well as the historical method of methods of inference and deduction to establish the facts and the impact of Imam Hussein’s speeches ( Peace be upon him) guided by sources and research in arriving at several conclusions, the most important of which are The impact of the speeches of Imam Hussein (peace be upon him) during his march to Karbala on the self-control of his companions and his household, and this was evident in all situations .The emergence of the social and educational reform project through the message of Imam Hussein (peace be upon him) to his brother Muhammad ibn al-Hanafiyya (I did not go out as evil, tyrannical, corrupt, or unjust. Rather, I went out to seek reform) The immortality of humanity's most gentle incident and its use in building societies and human beings searching for freedom and dignity.The Al-Taf incident is a real human tragedy that carries within it two dimensions: the emotional dimension and the ideological dimension, both of which have a great impact on the educational and intellectual structure of human societies.